Wednesday

August 27, 2014

August 27, 2014

Posted by **nathalie** on Monday, December 31, 2012 at 12:10pm.

x^5-3x^4-24x^3-72x^2-25x+75=0

5x^5-20x^4-40x^3-16x^2-45x+180=0

-3x^5+3x^4+9x^3-7x^2+12x=12

x^3-x^2-13x-13=0

x^3+x^2=15x-15

Thank you for any help...I'm desperate please help :(

- algebra 2 -
**TutorCat**, Monday, December 31, 2012 at 5:47pmFor the first three, you would have to apply the rational zero theorem ((Broken Link Removed) and then use synthetic division ((Broken Link Removed) to see if the remainder is zero.

For the last two, you would group the terms and factor out a common factor method(http://www.chesapeake.edu/khennayake/MAT113/3.2Solution.htm).

- algebra 2 -
**Henry**, Monday, December 31, 2012 at 8:58pmThis was done by trial and error assisted by EXCEL. Very tedious!

1.Solution Set: X =-1.5887,0.7772,-1.2089, and 0.8717.

2.X = -2.07316,1.2139,-5.0432, and 2.2307.

3. X = -1.9548,2.1191, and 0.9050.

4. X = -2.218,4.516,-11.908,-1.0917.

5. x^3+x^2 = 15x-15.

x^3+x^2-15x+15 = 0.

NOTE: All values of X shown are called

ZEROES, because they give zero output

when plugged into the Eq.

I hope I've helped.

X = -2.218,1.220,13.923,1.0774.

**Related Questions**

math,correction - Directions:Multiply Problem: ((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(...

Algebra - simpliy the following: (a) {[4x^2-49]/[8x^3+27]} *{ [4x^2+12x+9]/[2x^2...

calculus - i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x...

Algebra - Rewrite the middle term as the sum of two terms and then factor ...

Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

Algebra - 20x^2-12x+15x-9 20x^2-12x+15x-9 = 20x^2+3x-9 = (4x+3)(5x-3)

Algebra - Can someone tell me if I am right? Factor by group 20x^2-12x=15x-9 20x...

Urgent Math please check - Very Important I can get someone to check these for ...

someone help - my post is still on this page as algebra, could someone elaborate...